KEBIJAKAN BANTUAN SOSIAL ORGANISASI MASYARAKAT - Abdul Kadir E.21109027 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The problem in this study is that social grants are not based on forms of social organization as determined by the local government Kubu Raya district . In addition , the proposal approved organization communities receive social grants are not in accordance with the procedures and pendistrubusian funds held by SKPDs Kesbangpolinmas Kubu Raya district . This study aims to describe the process of policy implementation by the administration of social grants on education Kesbangpolinmas in Kubu Raya district . This type of research in this research is descriptive research that aims to obtain a systematic and accurate picture of the factors that has to do with implentasi policy . The research found that the procedures and pendistrubusian social grants for community organizations in the non- vertical Kubu Raya district regulations and policies issued by the local government office Kesbangpolinmas to distribute social grants directly through the bank accounts of community organizations whose proposals have been approved so there is no constraint retrieval funds if all requirements are met by the organization besangkutan . The end of the admission process of social grants when the community organizations that have received submit an accountability report in writing to the office Kesbangpolinmas with physical evidence and the use of funds already Kesbangpolinmas officers conduct a review into the field . Responding to the suggestion that there is a phenomenon that should be recommended during the distribution of social grants to community organizations Kesbangpolinmas has provided guidance and direction regarding the completion of the administrative process relating to the accountability and other physical evidence and the deadline for completion of the administration . If not complied will be given no sanction can apply for a social grant budget year . To strengthen this shared commitment needs to be made a statement by each society . This pattern aims to discipline the society in terms of administration in proposals so they are ready to follow the rules set Kesbangpolinmas. Keywords : Policy , Social Assistance , Community Organization .